A Tool for the Analysis of Market Power Potential in Electric Energy Markets - Borden, Alex (My University, 2010)
Market power is the ability of a market participant to alter the market price of a good or service without losing customers to competition. The participant's price is profitably maintained above a competitive level for a significant period of time. In ideal competitive markets, one would need to lower prices to garner more market share. In uncompetitive markets, participants who know their product is absolutely needed or not substitutable, can profitably raise prices to high levels [i]. In electric energy markets, there are many contributing factors determining competitiveness including market share, market concentration, elasticity of demand, excess capacity, contractual arrangements, price establishment processes and ease of market entry [ii]. The market participants in electric energy markets are the generators supplying electricity. Here the suppliers possessing market power potential can increase revenue without affecting the revenue and electric dispatch of other generators. When a centrally-dispatched electricity market is competitive, economic operation of the grid is transparent and efficient. However when a supplier possess an advantage over others, the benefits of a competitive electricity market may be jeopardized [ix]. Market power problems are complicated in electric markets due to specific properties of electricity and transmission grids [iii]. High concentrations of intensive power use can constrain transmission systems, and the ability of some loads to be served by generators located at remote distances would be limited. The areas where insufficient transmission capacity cannot reliably supply 100% of the electric load, without relying on generation physically located nearby, are termed "load pockets". Substitutability for the commodity is not readily available in these load pockets. Other sources of inefficiency are limited generation capacity of suppliers and a lack of sufficient energy storage. Generators that can capitalize on transmission deficiencies can iii increase price while maintaining their amount of energy sold. The constraints on the transmission grid allow one or more suppliers to exploit locational advantages to their benefit at the expense of the end user. There exist many tools widely used for identifying market power potential. Most rely on direct application of concentration measures, such as Residual Supplier Indices and the Hirschmann-Herfindahl Index, which show a single supplier or small number of suppliers dominating the market. These concentration measures are valuable but often fail to capture the true degree of competition [ix]. Concentration measures do not consider price-responsiveness or elasticity of demand, and a detailed representation of the electric grid may not be included. In electric energy markets various network operating limits often present market participants an uncompetitive advantage in small segments of the network, referred to as "local market power." Concentration measures may fail to identify these market participants exhibiting local geographic advantage when assessing the network as an aggregate [iv]. Distribution factors related to sensitivity of constrained lines and supplier dispatch are used in a PJM three pivotal supplier test that is said to be more accurate than concentration measures [v]. Here each constraint is examined individually to determine whether three suppliers are jointly pivotal in relieving the constraint. A similar approach will be taken in the algorithm of this paper, but will differ in that the simultaneous combined effect of all line constraints will be considered instead of evaluating one at a time. This new work is significant because the presence of multiple line constraints could further provoke market power potential, and these locational advantages may be less evident in the analysis of a lone constraint. The goal of this paper is to outline an algorithmic routine that exploits sensitivity analyses of coupled economic and physical models. Load demand is assumed to be inelastic, iv and only the effect of offer price on the market is studied. Limits are placed on transmission lines known to be easily congested, and a linear programming optimal flow is run. Matrices of dispatch/offer price and revenue/offer price sensitivities are then calculated for further evaluation which will highlight suppliers able to manipulate the market to their advantage. This analysis does not necessarily conclude certain generators are exercising market power or to what extent this potential may be exercised. It serves as a screening tool so that dominant suppliers flagged can be investigated for the possibility of market power potential. The impact of this work will improve the efficiency and reliability of the electric power grid.